PREDETERMINACY AND RELATIONS BETWEEN HISTORICAL EVENTS AND NATURAL PROCESSES ON THE EARTH AND IN THE SOLAR SYSTEM (ABOUT BOOK SERIES ON THE CHRONOLOGY OF NATURAL PHENOMENA, GEODYNAMICS AND HELIOGEODYNAMICS) - Yu. G. Gatinsky (Геодинамика и тектонофизика)
.